The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1590/s0080-623420160000300004
|View full text |Cite
|
Sign up to set email alerts
|

Medical training and nurses of Family Health strategy on worker health aspect

Abstract: Considering the worker’s health one of the Unified Health System (SUS) tasks, the Primary Health Care (PHC) and the Family Health Strategy (FHS) play an important role in the development of health actions in the field health-work. In Brazil, where the number of informal and domiciled jobs is high, the FHS becomes a reference in the workers’ health actions. Therefore, if the FHS is not attentive to the relation between professional occupation and disease, several diseases that affect workers can overload the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…A força de trabalho necessária para a execução do processo de trabalho de enfermeiros na saúde do trabalhador é citada na maioria dos estudos e em todas as categorias como uma equipe multiprofissional (Dombrowski et al, 2014;Rogers et al, 2014;Rogers, 2012;Castro et al, 2015;Wolf et al, 2014;Mizuno-Lewis et al, 2014;McCullagh, 2012;Hong, 2012;Strasser, 2012;Macedo et al, 2015;Alexander, 2013;Burgel et al, 2013;Kinnunen-Amoroso & Liira, 2014;DeAngelis & Burgel, 2013;Burgel & Childre, 2012;Harber et al, 2014). Isto pode estar vinculado ao fato da saúde do trabalhador exigir, dos profissionais enfermeiros, conhecimentos que vão além da clínica e dos cuidados de enfermagem (Mori & Naghettini 2016).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A força de trabalho necessária para a execução do processo de trabalho de enfermeiros na saúde do trabalhador é citada na maioria dos estudos e em todas as categorias como uma equipe multiprofissional (Dombrowski et al, 2014;Rogers et al, 2014;Rogers, 2012;Castro et al, 2015;Wolf et al, 2014;Mizuno-Lewis et al, 2014;McCullagh, 2012;Hong, 2012;Strasser, 2012;Macedo et al, 2015;Alexander, 2013;Burgel et al, 2013;Kinnunen-Amoroso & Liira, 2014;DeAngelis & Burgel, 2013;Burgel & Childre, 2012;Harber et al, 2014). Isto pode estar vinculado ao fato da saúde do trabalhador exigir, dos profissionais enfermeiros, conhecimentos que vão além da clínica e dos cuidados de enfermagem (Mori & Naghettini 2016).…”
Section: Resultsunclassified
“…Em relação ao objeto de trabalho, foi possível constatar que, na perspectiva gerencial, os enfermeiros têm atuado na transformação/adaptação de recursos humanos (trabalhadores) (Dombrowski et al, 2014;Michell, 2012;Thompson & Wachs, 2012;Rogers et al, 2014;Hong et al, 2013;Rogers, 2012;Castro et al, 2015;Wolf et al, 2014;Mizuno-Lewis et al, 2014;McCullagh, 2012;Hong, 2012, financeiros (Rogers et al, 2014 e de infraestrutura dos serviços de saúde e dos ambientes de trabalho (Dombrowski et al, 2014;Research, Society and Development, v. 9, n. 8, e158985590, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.5590 enfermeiros que não se restringe somente ao cuidado ao trabalhador (Oliveira et al, 2014), e destaca a inserção destes profissionais na gestão (Mori & Naghettini, 2016) da saúde do trabalhador e, consequentemente, na linha de frente dos atendimentos das necessidades desta área da saúde (Tronchin et al, 2015).…”
Section: Resultsunclassified
“…In a study by Mortenson, availability of caring behaviors was given the highest prominence (18). One of the strongest factors underlying the increase in the capacity of the medical team is the improved communication between the patient and the treatment team, as this relationship will not only help identify patients' needs but also will identify their work capacity (19).…”
Section: Discussionmentioning
confidence: 99%
“…In this category, eight articles were included, 11,13,15,[17][18][19][20][21] which corresponds to 42% of the number of articles analyzed. In this context, it was observed that Permanent Health Education (PHE) can be a protective factor for workers, and one of the areas of greatest need to implement practices in PHE is mental health.…”
Section: Discussion Actions Aimed At Permanent Education In Healthmentioning
confidence: 99%
“…In this context, it was observed that Permanent Health Education (PHE) can be a protective factor for workers, and one of the areas of greatest need to implement practices in PHE is mental health. 11,13,17,19,20 Here, therefore, a relationship is established between PHE actions and the health of FHS workers, including health promotion, prevention and mental health care.…”
Section: Discussion Actions Aimed At Permanent Education In Healthmentioning
confidence: 99%